Prevalence of Plasmid-mediated Quinolone Resistance (PMQR) Genes and Beta-lactamase Genes among Salmonella, Vibrio parahaemolyticus and Escherichia coli from Shellfish - Divya, Sukumaran P.; Chandradasan, Athira; Pranav, P. K.; Antony, Ally C.; Mohamed Hatha, A. A. (Fishery Technology, 2020)
The objectives of the present study were to investigate the prevalence of plasmid-mediated quinolone-resistance (PMQR) genes and betalactamase genes in Salmonella, Vibrio parahaemolyticus and Escherichia coli from shellfish. A total of 35 Salmonella, 22 Vibrio parahaemolyticus, and 58 Escherichia coli of shellfish origin were used in this study. Antibiotic susceptibility testing of Salmonella, V. parahaemolyticus, and E. coli against different antibiotics was determined by disc diffusion method. The minimum inhibitory concentrations (MIC) of nalidixic acid and ciprofloxacin were analyzed by microdilution method for all nalidixic acid/ ciprofloxacin-resistant strains. All the isolates were screened for the presence of PMQR genes (qnrA, qnrB, qnrS, qepA, aac(6’)-Ib-cr, and oqxA) and betalactamase genes (blaTEM, blaSHV, and blaCTXM-1). The prevalence of nalidixic acid resistance was 5.7, 9, and 3.4% in Salmonella, V. parahaemolyticus and E. coli, respectively. Approximately, 4.5% of V. parahaemolyticus isolates were resistant to ciprofloxacin. The prevalence of PMQR harboring Salmonella, V. parahaemolyticus, and E. coli was 22, 9 and 3% respectively. The prevalence of betalactamase genes in Salmonella, V. parahaemolyticus, and E. coli were 17.14, 9 and 5.1%, respectively. The most prevalent PMQR and beta-lactamase genes were qnrS and blaTEM, respectively. The co-occurrence of PMQR and beta-lactamase genes in V. parahaemolyticus and Salmonella, from shellfish, poses a public health concern.